Beyond The Binary: Reconfiguring Gender Roles in Angela Carter’s “The Bloody Chamber” - Bhatta, Laxman; Mahato, Ramesh Kumar (Tribhuvan University Journal, 2025)
This research paper examines how the story “The Bloody Chamber” from Angela Carter's The Bloody Chamber and Other Stories (1979) subverts traditional notions of gender and sexuality. By destabilizing the binary oppositions of male and female, Carter challenges the patriarchal hierarchy that relegates women to secondary positions. Through role reversals, gender blending, and the blurring of subject object distinctions, Carter's story explores the complexities of gender identity and agency. Drawing on theoretical insights from Judith Butler, Judith Halberstam, and Michel Foucault, this paper contends that Carter's work is a powerful critique of heteronormative discourses and a call for reconfiguration of restrictive gender roles.